Analisis Peluang dan Tantangan Dalam Hal Pengembangan Konten Dakwah Dalam Era AI - Hidayat, Garneta Edlyn Putri; Sundah, Muhammad Aksan Fawwaz; Setiadi, Kaka Putra; Faqihuddin, Achmad (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The development of Artificial Intelligence (AI) has had a significant impact on various aspects of life, including Islamic preaching (dakwah). This study aims to analyze the opportunities and challenges of utilizing AI in the development of dakwah content in the digital era, particularly among the younger generation. Using a qualitative research method with a descriptive approach, data were collected through in-depth interviews with eleven participants consisting of students, lecturers, and dakwah activists within the Faculty of Technology and Science Education (FPTI) at the Indonesia University of Education (UPI). The findings indicate that AI is perceived as a potential tool to accelerate, expand, and simplify the dissemination of religious messages through creative formats such as short videos, podcasts, animations, and Islamic chatbots. Respondents believe that AI can make dakwah more adaptive, interactive, and relevant to the needs of the digital generation. However, the study also identifies several critical challenges, including the risk of misinformation, AI’s limitations in capturing spiritual dimensions and scholarly lineage (sanad), and the potential reduction of dakwah into mere superficial entertainment. Therefore, AI should be positioned as a strategic assistive tool in dakwah, not as a replacement for the authority of scholars (ulama) and preachers (da’i), who continue to play a central role in preserving the authenticity of Islamic messages. The study concludes that the use of AI in dakwah holds positive prospects if managed ethically, critically, and responsibly through collaboration among preachers, dakwah institutions, and technology developers.